Attention shifts during action sequence recognition for social robots - Khadhouri,B; Demiris,Y (IEEE, 2005)
Human action understanding is an important component of our research towards social robots that can operate among humans. A crucial element of this component is visual attention - where should a robot direct its limited visual and computational resources during the perception of a human action? In this paper, we propose a computational model of an attention mechanism that combines the saliency of top-down elements, based on multiple hypotheses about the demonstrated action, with the saliency of bottom up components. We implement our attention mechanism on a robot, and examine its performance during the observation of object-directed human actions. Furthermore, we propose a method for resetting this model that allows it to work on multiple behaviours observed in a sequence. We also implement and investigate this method's performance on the robot.